ANTECEDENTS DAN CONSEQUENCES DARI ATTITUDE TOWARD POP-UP RETAIL - Andriyani Andriyani (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
The background of this research is to observe the impact of psychographic characteristics and behavioral intentions toward pop-up retail. The order of life is growing, consumers have a desire to increase the role ofself developed, innovate, and open-mindedness toward difference and unique experiences. Marketingenvironmental uniqueness that offered by pop-up retail can be attract consumer to find the difference wayand innovative experiences.The objectives of this research are to observe the impact of psychographic characteristics toward behavioralintentions through beliefs and attitude in Pekan Raya Jakarta pop-up retail.Structural Equation Model (SEM) method with parceling technique is used to analyzed the data of thisresearch. The data were collected by distributing closed questionnaires to Jakarta community respondents who ever visit into Pekan Raya Jakarta. There were 200 from 230 questionnaires data of respondent can beanalyzed in this research.The result of this research concludes that had any positive influence on psychographic characteristicsdimensions and beliefs although towards consumer attitude dan intention to patronage pop-up retail.